THE USE OF VISUAL MEDIA IN TEACHING VOCABULARY - Newin Mardianti; Eliza Eliza (Universitas Mahaputra Muhammad Yamin, 2022)
The purpose of this study was to determine the efficacy of employing visual media in teaching vocabulary mastery in the seventh grade at UPT SMPN 3 Lunang. Several issues with students' vocabularies were discovered in the field. They were students' lack of motivation in expanding their English vocabulary, restricted vocabulary, and losing previously taught vocabulary. During the learning process, the researcher used visual media such as photos and actual objects to help students with vocabulary mastering. This study used descriptive quantitative research.The participants in this study were all UPT SMPN 3 Lunang students in the seventh grade. To collect the data, researcher used a test vocabulary from students. Based on calculated the data, the result of mean score vocabulary mastery students was 75 included at level effective. Therefore, it can be concluded using visual media effective for students vocabulary at seventh grade of UPT SMPN 3 Lunang.